Faktor-Faktor Yang Mempengaruhi Audit Switching : Opini Audit, Ukuran KAP Dan Audit Delay - M Erbi Farel KH; Cris Kuntadi (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
This research aims to investigate the factors that influence companies in carrying out audit switching or changing auditors. Specifically, this research analyzes the influence of audit opinion, size of the Public Accounting Firm (KAP), and audit delay on a company's decision to change auditors. The issue of audit switching is important considering the existence of regulations that require regular rotation of auditors to maintain audit independence. Using a sample of companies listed on the Indonesia Stock Exchange, this research applies a logistic regression model to test the influence of independent variables (audit opinion, KAP size, and audit delay) on the dependent variable, namely audit switching. The data used comes from financial reports and company audit reports.